Novel useful markers for follow-up of necrotizing enterocolitis: endocan and interleukin-33. (17th July 2020) - Cakir, Ufuk; Tayman, Cuneyt; Yarci, Erbu; Halil, Halid; Buyuktiryaki, Mehmet; Ulu, Hulya Ozkan; Yucel, Cigdem; Oguz, Serife Suna
Abstract: Objectives: To ascertain the diagnostic value of endocan and interleukin (IL)-33 in infants with necrotizing enterocolitis (NEC) and to compare their effectiveness with C-reactive protein (CRP) and interleukin-6 (IL-6). Methods: Eighty-four preterm infants including control ( n = 42) and NEC ( n = 42) were eligible. Blood samples were obtained from infants in the NEC for the assessment of CRP, IL-6, endocan, and IL-33 serum levels at the time of diagnosis (first day), at the third and seventh days of NEC. Endocan, IL-33, CRP, and IL-6 serum levels were measured at the 14th day of life in the control group. Results: Serum levels of endocan, IL-33, CRP, and IL-6 were significantly higher in the NEC group compared to the control group at the first, third, and seventh days ( p < .05). IL-33 and endocan levels continued to rise in the consequent days in patients with stage III NEC ( p < .05). Serum endocan and IL-33 levels gradually increased in patients who underwent surgery ( p < .05). Serum endocan levels were higher in patients with stage III NEC than those in the stage II NEC at the diagnosis. Conclusions: Serum levels of IL-33 and endocan can be used as markers in the diagnosis and follow-up of NEC.